Rātib al-Ḥaddād and Alternative Healing: A Living Qur'an Study at the Miftahut Taubah Dhikr Assembly, Deli Serdang - Egi Alhadi; Munandar Munandar (Fakultas Agama Islam, 2026)
The proliferation of Islamic-based healing practices among the public presents a dilemma between the pragmatism of alternative medicine and the potential risk of theological deviation resulting from a lack of textual analysis regarding the practices employed. This study aims to examine the integration and textual foundation of the recitation of Rātib al-Ḥaddād at the Majelis Dzikir Miftahut Taubah (MDMT) in Sukamandi Village, Deli Serdang. Employing a qualitative case study design with a Living Qur'an approach, data were gathered through participant observation, in-depth interviews with practitioners and congregants, and textual-activity documentation of the assembly. The findings reveal that the recitation of Rātib al-Ḥaddād at MDMT possesses a robust normative foundation, fully legitimized under Islamic jurisprudence (sharīʿah) through evidence from the Qur'an, Hadith, and scholarly consensus. The perceived therapeutic efficacy for both somatic and non-somatic ailments relies on an elevated consciousness of Islamic monotheism (tawḥīd), the intrinsic virtues (faḍīlah) of the texts, and the principle of takhṣīṣ al-istiʿmāl embedded within Sūrah al-Fātiḥah, al-Muʿawwidhatayn, specific supplications (dhikr and duʿā), and blessings upon the Prophet (ṣalawāt). Furthermore, the use of water as a therapeutic medium is positioned purely as a permissible physical endeavor (ikhtiyār sharʿī), with ultimate efficacy attributed solely to God (Allāh). This study argues that Islamic spiritual-alternative healing must transcend mere physical recovery to prioritize spiritual re-orientation, thereby reaffirming the Qur'an as al-Shifāʾ (the healing source) while safeguarding the theological purity of the practitioners' faith (ʿaqīdah).